Female Identity and Marginalization in the God of Small Things: A Review: Exploring Women's Marginalization in Arundhati Roy's God of Small Things (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Arundhati Roy’s The Good of Small Things is a rare work of fiction which has made a significantimpact in Indian English Literature in recent years. She is one of the few Indian English writersenthusiastically interested in contemporary socio-political issues which are adequately documented in anumber of articles, interviews and books she authored on various topics in recent years. Indian history,politics, caste distinction, and suppression woman and her independence as human being, all thesedistinct elements are brought together by Roy, to shed vivid light on the plight of women and how theylive under oppressive forces including their relationships with men who control them. There is noexaggeration to say that women are treated as an object of lust and sexual gratification. They are robbedof basic amenities of life. They are forced to live in a system of social structure and practices in whichmen dominate, oppress, and exploit women.This present paper is an attempt to have a review of female identity and marginalization in Roy’s God ofSmall Thing, which has been widely acclaimed as an important book of the post-modernist literary trend